Scavenger templates: a systems chemistry approach to the synthesis of porphyrin-based molecular wires - Cnossen, A; Roche, C; Anderson, H (Royal Society of Chemistry, 2017)
A hexa-pyridyl template can be used as a scavenger to facilitate the synthesis of a linear porphyrin dodecamer from a mixture of linear hexamers with one or two terminal reactive groups. The template suppresses polymer formation by rapidly cyclizing the fully deprotected hexamer, thus upregulating formation of the linear dodecamer.